A COMPREHENSIVE REVIEW OF Apium graveolens (CELERY) PLANT: PHARMACOTHERAPY AND HEALTH PERSPECTIVES (International Journal of Food and Nutritional Sciences, 2023)
Apium plants belong to the Apiaceae family and have been integral to traditional medicine across the Mediterranean, tropical, and subtropical regions of Asia and Africa for millennia. They are valued for their medicinal benefits, particularly in preventing coronary and vascular disorders. Apium plants are rich in phytochemicals such as bergapten, flavonoids, glycosides, furanocoumarins, furocoumarin, limonene, psoralen, xanthotoxin, and selinene. These plants exhibit diverse pharmacological properties including anticancer, antioxidant, antimicrobial, antifungal, nematocidal, anti-rheumatic, antiasthmatic, anti-bronchitic, hepatoprotective, appetizer, anticonvulsant, antispasmodic, lactation-inducing, anti-jaundice, antihypertensive, anti-dysmenorrheal effects, as well as promoting cardiovascular health and spermatogenesis. This review synthesizes information on the ecology, botany, cultivation practices, natural habitat, medicinal properties, phytochemical composition, and pharmacological efficacy of Apium plants, aiming to optimize their therapeutic potential for human health.